Excellence in Agronomy - International Institute of Tropical Agriculture (CGIAR Excellence in Agronomy Initiative, 2022)
Excellence in Agronomy is a CGIAR-wide initiative that seeks to accelerate the uptake of validated agronomic solutions at scale. Our vision is smallholder farming that is on a path towards sustainable intensification and climate change adaptation. We seek to leverage the power of science, data analytics and latest advances in digital solutions to reach larger numbers of farmers with the solutions they need, in a manner that is accessible and useable.